Digital Storytelling in Education: A Transmedia Integration Approach for the Non-Developers - Maria Palioura; Charalampos Dimoulas (MDPI AG, 2022)
The present paper focuses on digital storytelling in education, emphasizing the teachers' needs for familiarization with the new technological conditions. A transmedia integration approach is deployed to make productive, blended learning values while utilizing the availability of tools and reusable media assets in a component-based software engineering kind of framework. The topic is inspired by social studies and humanities, which seem to be marginalized, usually failing to make effective technological facilities, benefits, and contemporary findings. It is, therefore, necessary to modernize the approach to literary things and integrate digital means into the educational process, even in cases where a sole educator on humanities and social studies lacks multidisciplinary support in multimedia authoring and software engineering. This modernization can be made possible by introducing user-friendly tools into the process, representing not just a fashion of the time but mostly a renewal trend, aiming at revitalizing the course to attract and engage learners. Undoubtedly, today's pupils have grown up with technological means, becoming familiar with their use so their implication causes undiminished interest in most daily activities, including schooling. In this high-tech generation, it is absurd to address the transmission of knowledge and values in outdated ways. Apart from adapting to the timely students' needs, lesson plans on transmedia storytelling practices can also satisfy tutors, triggering their inspiration and co-creation potentials. Overall, the project aims to attract the trainees' interest with the help of digital tools, which will be embodied in the educational processes by teachers without technical know-how, while continuously adapting to the audience's needs. Research hypothesis and questions are formed as part of the deployed human-centered interactive design, aiming at modeling best practices for teaching classical topics, such as the "Odyssey".